How to think about excerise - Young, Damon, ....- (London : Macmillan, 2014)
This book answers the question of exercise by examining our modern lifestyles of new technology and expensive gym memberships, of commuter trains and air-conditioned offices. It then goes further by asking us to reflect on the mental value of exercise. Drawing on scholarship, great literature and pop culture, he examines different forms of exercise and reveals how physical activity can be existential, a way of reclaiming and refining ourselves.
Keywords: Sport ; filosofie